Measuring the effectiveness of various sensors in its deployment to the judging system in badminton / Ayu Hj Sopin - Sopin, Ayu (2006)
Today, we still needs line judges in giving point for badminton game. We have to use 10 line judges and 1 service judges. Even though, as a human sometimes we can careless, slack, emotional not stable and it can give bad impact for the players in giving point. The objective of this project is to measure from all types of sensors which one of them will be suitable for reduce line judges especially at critical line that judges sometimes careless in giving point. This project gives benefit for the players and also will increase sport quality especially in badminton games. Using the suitable sensor, it will make giving point is more accuracy and will prevent biased judges.